Volume 2: Materials; Biomanufacturing; Properties, Applications and Systems; Sustainable Manufacturing 2015
DOI: 10.1115/msec2015-9384
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sustainable Design-Centered Factors for Manufacturing Bioprinting Material of Polylactic Acid

Abstract: Sustainable design-centered manufacturing (SDM) is a competitive advantage for new product development. In this research, we determine the SDM factors for Polylactic Acid (PLA) production from cradle to gate. PLA is a mainstream material for bioprinting. We utilize a holistic method to determine the most sensitive and significant sustainability factors among economic, environmental, and social pillars, by adopting ISO 14040 and 14044 frameworks, life cycle cost analysis, and regression analysis methods. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…PLA can be recyclable several times, releasing no toxic fumes when it oxygenates and providing a sweet aroma at printing [37,38]. During the 3D printing process, most petroleum-based plastics release toxic substances and evaporated particles [46]. On the other hand, PLA is not related to any toxic or carcinogenic effect, which positively influences human health and the environment [27,37,47].…”
Section: Sustainability Perspective Of Bio-based Vs Petroleum-based P...mentioning
confidence: 99%
See 1 more Smart Citation
“…PLA can be recyclable several times, releasing no toxic fumes when it oxygenates and providing a sweet aroma at printing [37,38]. During the 3D printing process, most petroleum-based plastics release toxic substances and evaporated particles [46]. On the other hand, PLA is not related to any toxic or carcinogenic effect, which positively influences human health and the environment [27,37,47].…”
Section: Sustainability Perspective Of Bio-based Vs Petroleum-based P...mentioning
confidence: 99%
“…Fermentation routes for the production of intermediate starting materials have also been reported [39,56]. Even though it is derived from a biobased starting material, nylon 11 is not easily biodegraded, although nylon 11 blends and composites can be biodegraded [46,58]. Previous work by Saloni et al [29] has shown the importance and relevance of additive manufacturing and the sustainable relevance of using bioplastics [10].…”
Section: Market Growth Of Biodegradable Plastics Used In Additive Man...mentioning
confidence: 99%
“…The industries are in a constant search for non-oil products, using renewable resources and considering the environmental impacts during the life cycle (Simões et al, 2013;Wang et al, 2015). According to Luz et al, (2010) the production of goods with natural fibers is also considered a great opportunity for social and economic progress in developing countries, promoting the livelihood of millions of small farmers and low-paid workers.…”
Section: Environmental Benefitsmentioning
confidence: 99%